BIOTECHNOLOGICAL METHODS FOR ENSURING MICROCLIMATE STANDARDS IN LIVESTOCK BUILDINGS - БРАТІШКО, ВЯЧЕСЛАВ; BURLAKA, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines biotechnological methods for ensuring microclimate standards in livestock buildings as an effective alternative to traditional ventilation and air conditioning technologies.Maintaining optimal microclimate parameters, such as temperature, humidity, air gas composition, and the level of biological contamination, is a critical factor in ensuring high productivity and health of farm animals.The study investigates the impact of biofilters, microorganisms for biodegradation of harmful gases (ammonia, hydrogen sulfide, methane), biodynamic composting, and natural sorbents on stabilizing microclimate parameters. Biofilters using active microorganisms can effectively neutralize toxic gases, reducing negative impacts on animals and personnel. Biodynamic composting helps reduce greenhouse gas emissions and unpleasant odors while producing organic fertilizers that can be used in agriculture.The article explores the potential of using phytosystems and aerobic microorganisms for air purification, reducing pathogenic microorganism concentrations, and regulating humidity. The use of biologically active materials, such as zeolites, peat, and activated carbon, allows for effective absorption of excess moisture and toxic gases, positively influencing microclimate parameters.Special attention is given to the automation and monitoring of these processes to enhance energy efficiency and environmental safety of livestock complexes. The implementation of sensor systems that monitor key microclimate indicators and automated biotechnological installations ensures the stability of the animal housing environment, reducing energy costs and minimizing environmental impact.The obtained results can be used to develop innovative microclimate management systems that combine biotechnological solutions, automation, and energy-efficient technologies. The application of such approaches will contribute to increasing animal productivity, improving their health, and ensuring sustainable livestock development.
Keywords: mechatronic systems; airflows; temperature; humidity; microclimate; livestock building; automation; ventilation; heat exchange; mass transfer; pressurization; energy efficiency